Pengaruh Psikologi Konsumen Terhadap Keputusan Pembelian Kembali Smartphone Blackberry - Bunga Geofanny Fredereca; Chairy Chairy (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2010)
Repurchase decision is influenced by several factors, among others are, marketing stimuli (marketing mix) environmental stimuli, consumer characteristics, and consumer psychology. Previously, marketers were more interested in studying consumer response to marketing mix. This study investigated the influence of consumer psychology on repurchase decision. The independent variables of the research are motivation, perception, learning, and attitude. The dependent variable is the repurchase decision of the BlackBerry. Data were collected by distributing questionnaires to 200 BlackBerry smartphone users. Data analysis was performed using multiple regression. The results showed that there is only one variable (attitude) that has a significant influence on repurchase decision. Thus, marketers with limited budgets need to be more selective in allocating their funds, which is primarily should be intended to build and develop positive attitudes towards BlackBerry.